\[\boxed{\text{327\ (327).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[График\ y = x^{2}\ представим\ в\ \]
\[виде\ y = (x - a)^{2} + b;\]
\[где\ a,\ b - смещение\]
\[вершины\ параболы\ \]
\[(она\ же\ точка\ вершины\ параболы).\]
\[\textbf{а)}\ y = (x + 2)^{2} - 4\]
\[\textbf{б)}\ y = - (x - 2)^{2} + 5\ \]
\[\textbf{в)}\ y = \frac{1}{3} \cdot (x - 3)^{2} + 1\ \]
\[\boxed{\text{327.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ f( - 3,5) = - 0,5\]
\[f( - 2,5) = 2\]
\[f( - 1) = 0\]
\[f(2) = - 1\]
\[2)\ f(x) = - 2,5 \Longrightarrow \ \ x = 5\]
\[f(x) = - 2 \Longrightarrow \ x = 3,5\]
\[f(x) = 0 \Longrightarrow \ \ x = - 3;\ \]
\[x = 1,5;\ x = - 1\]
\[f(x) = 2 \Longrightarrow \ \ x = - 2,5;\ \]
\[x = - 1,5;\ \ x = 0\]
\[3)\ E(y) = \lbrack - 2,5;3\rbrack\text{.\ }\]